2015
DOI: 10.1155/2015/315495
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Child Agreement Using the Spence Children’s Anxiety Scale and a Thermometer in Children with Autism Spectrum Disorder

Abstract: Children with Autism Spectrum Disorder (ASD) experience high anxiety which often prompts clinical referral and requires intervention. This study aimed to compare parent and child reports on the Spence Children's Anxiety Scale (SCAS) and a child-reported “worry thermometer” in 88 children aged 8–13 years, 44 with ASD and 44 age, gender, and perceptual IQ matched typically developing children. There were no gender differences in child report on the SCAS and worry thermometers. Results indicated generally good co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 49 publications
(67 reference statements)
3
13
0
Order By: Relevance
“…Regarding the first theory, it is not clear whether the chosen measures used in the study for the adults with ASD were inappropriate given that the research findings on the validity of self-report measures of anxiety for the ASD population are equivocal. Some studies find that self-report ratings made by youth with ASD are equally accurate to parent-report ratings of anxiety symptoms (Ozsivadjian et al 2014), other studies reveal that children with ASD are more accurate at reporting on their anxiety because their ratings correlate better with their levels of the stress hormone cortisol compared to parent-report ratings (Bitsika et al 2015), and still other investigations find that self-report relative to parent-report ratings less accurately reflect anxiety symptoms (May et al 2015). Given these inconsistent findings, further study of measurement validity in ASD is crucial, as valid measures of internalizing symptoms would enable researchers to more accurately assess the treatment effects of intervention studies for ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the first theory, it is not clear whether the chosen measures used in the study for the adults with ASD were inappropriate given that the research findings on the validity of self-report measures of anxiety for the ASD population are equivocal. Some studies find that self-report ratings made by youth with ASD are equally accurate to parent-report ratings of anxiety symptoms (Ozsivadjian et al 2014), other studies reveal that children with ASD are more accurate at reporting on their anxiety because their ratings correlate better with their levels of the stress hormone cortisol compared to parent-report ratings (Bitsika et al 2015), and still other investigations find that self-report relative to parent-report ratings less accurately reflect anxiety symptoms (May et al 2015). Given these inconsistent findings, further study of measurement validity in ASD is crucial, as valid measures of internalizing symptoms would enable researchers to more accurately assess the treatment effects of intervention studies for ASD.…”
Section: Discussionmentioning
confidence: 99%
“…The RCMAS-2 is a self-report measure containing 37 items to assess total anxiety as well as subscales of physiological anxiety, worry, and social anxiety. Although concerns exist regarding the ability of adolescents with ASD to report accurately on their own internalizing symptoms (May et al 2015), recent studies have demonstrated reasonable parent-adolescent agreement on internalizing measures (Blakeley-Smith et al 2012; Ozsivadjian et al 2014) and emphasized the value of self-report in this population. Eleven adolescents provided RCMAS-2 data at age 14 years.…”
Section: Methodsmentioning
confidence: 99%
“…Additional concerns have been raised in the examination of anxiety measures at the scale and subscale levels; there has been some empirical investigation of reporter (caregiver vs. child) discrepancies of anxiety in ASD, yet findings in the literature are mixed. Some suggest that parents report higher anxiety levels (Lopata et al, 2010), lower anxiety levels (Hurtig et al, 2009; Ooi et al, 2016; White, Schry, et al, 2012), and the same mean anxiety level (Burrows et al, 2018; May, Cornish, & Rinehart, 2015) compared with their child with ASD.…”
Section: Assessing Social Anxiety In Autism Spectrum Disordermentioning
confidence: 99%